THE INFLUENCE OF BOARD CHARACTERISTICS ON CSR DISCLOSURE: AN EMPIRICAL STUDY OF THE FINANCIAL SECTOR IN INDONESIA - Santoso, Eko Budi; Hariyono, Cherish Sheverine (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study examines how the characteristics of a company's board of directors affect Corporate Social Responsibility (CSR) reporting in 104 Indonesian financial firms listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. It explores how factors like board gender diversity, age, size, tenure, financial expertise, and narcissism influence CSR disclosure. The research focuses on the board of directors because in their roles as decision-makers, especially in shaping CSR strategies and reporting. By analyzing these characteristics, the study aims to understand how the board's characteristics impact their decisions related to CSR. Despite the financial sector’s relatively low environmental impact, its strong CSR performance raises critical questions about the authenticity of its disclosure, which is the focus of this research. A key innovation of this study is its use of these regulations as a benchmark for measuring CSR, alongside its exclusive focus on board characteristics in the financial sector. By analyzing the connection between board of directors’ characteristics and CSR disclosure, the findings aim to provide valuable insights for investors, government agencies, regulators, and CSR institutions. Ultimately, this research explores how board characteristics influence the transparency of CSR disclosures in Indonesia's financial industry.